Single women's happiness in terms of social support and religiosity - Islahiani Rufaidah; Setiasih Setiasih (An-Nisa’ Journal of Gender Studies, 2024)
In Indonesia, single women continue to face negative stigma. They are often perceived as "incomplete" individuals for being unmarried or not wishing to marry. Society tends to view single women with concern, although they may still experience happiness through the social support and religiosity they possess. This study aimed to examine the relationship between social support and religiosity with happiness among single women. A quantitative approach was employed using an online survey of 82 single women selected through purposive sampling. Standardized instruments were used, and data were analyzed using parametric statistical methods with SPSS. The results revealed a significant positive relationship between social support and religiosity with happiness among single women (r = 0.650). Higher levels of both factors were associated with greater happiness. Social support helps mitigate external stigma, while religiosity provides positive meaning to singlehood, reduces stress, and enhances happiness. The study concludes that social support and religiosity are positively related to happiness in single women, with the majority of participants falling into the moderate category and religiosity emerging as a more prominent internal factor. This study contributes to social exchange theory and expands the understanding of religiosity as a coping mechanism, offering practical implications for developing social support systems, psychological interventions, and more inclusive public policies toward single women.